The impact assessment of anticancer drug imatinib on the feeding behavior of rotifers with an integrated perspective: Exposure, post-exposure and re-exposure. (October 2017) - Yan, Zhengyu; Yan, Kun; He, Xingliang; Liu, Yanhua; Zhang, Jie; Lopez Torres, Oscar; Guo, Ruixin; Chen, Jianqiu
Abstract: The anticancer drugs are getting increasing attention as an emerging contaminant in the aquatic environments. In the present study, feeding behavior of the rotifer Brachionus calyciflorus under the impact of anticancer drug imatinib was evaluated. Traditional toxicological studies usually focus on dose-effect relationship at a given exposure time, while ignore the possible impact after the exposure. Thus, how the impact varied in the post-exposure and re-exposure was also considered in the present study. The feeding depression of the rotifers was attributed to the increased concentration of imatinib. Although the filtration and ingestion rate of the rotifers recovered to a certain extent after the exposure, the significant feeding inhibition still persisted even if the exposure was ended. In the re-exposure period, the feeding behavior was less depressed than those of the exposure period, which implied that rotifers might develop a tolerance to the same toxics. The activities of acetylcholine esterase (AchE) and the levels of reactive oxygen species (ROS) in rotifers were also detected. Imatinib inhibited the activities of AchE in the exposure and re-exposure while ROS levels increased significantly in the re-exposure period. Our present study provided an integrated assessment the potential environmental risks of imatinib at a new perspective. Graphical abstract: Highlights: Feeding depression of the rotifer was attributed to the concentration of imatinib. Feeding depression occurred in the post-exposure and re-exposure period. Activity of AchE increased in the recovery as overcompensation effect. ROS increased significantly in the re-exposure period.